The Relationship Between Blood Glucose and Increased Total Cholesterol in Outpatients at the Telaga Biru Community Health Center in Pontianak - Anjela Zotti; Etik Nurhayati; Ratih Indrawati (Public Health Frontier, 2026)
Blood glucose and total cholesterol are two important indicators of body metabolism that are interrelated. High blood glucose levels over a long period of time can affect lipid profiles, including increasing total cholesterol levels. This study aims to determine the relationship between blood glucose levels and increased total cholesterol in outpatients at the Telaga Biru Public Health Centre in Pontianak. This study used a quantitative approach with a cross-sectional design. Blood glucose tests were performed using the GOD-PAP (Glucose Oxidase-Peroxidase Aminoantipyrine Phenol) method, while total cholesterol levels were tested using the CHOD-PAP (Cholesterol Oxidase-Peroxidase Aminoantipyrine Phenol) method using a spectrophotometer. Thirty respondents were selected through accidental sampling. Data were statistically analysed using Fisher's exact test. The results showed that 50% of respondents (15 people) had abnormal (high) blood glucose levels, i.e., >115 mg/dl, while 26.7% of respondents (8 people) had abnormal (high) total cholesterol levels, i.e., >200 mg/dl. The Fisher's exact test showed a significance value of 0.035 (p < 0.05). Based on the statistical analysis, it can be concluded that there is a significant relationship between blood glucose levels and increased total cholesterol in outpatients at the Telaga Biru Public Health Centre in Pontianak.